Metode Pembiasaan dan Keteladanan Melalui Kegiatan Berbagi Dalam Meningkatkan Kemampuan Sosial Emosional Anak Usia 4-5 Tahun - Rohmatin, Islah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to determine the social-emotional abilities of 4–5-year-old children at TK Pertiwi Padamenak, to explore the habituation and exemplary methods applied by teachers at school, and to identify the habituation and exemplary practices implemented by parents at home. The research method used is a qualitative approach with a case study design. The research subjects include the principal, classroom teacher, and parents, while the object of the research is the children's social-emotional abilities. Data collection techniques involve observation, interviews, and documentation. Data analysis techniques are carried out using inductive and deductive reasoning. The results show that through habituation and exemplary methods in sharing activities, children gradually develop better abilities in expressing feelings, controlling emotions, and social interaction. In conclusion, consistent habituation and exemplary practices by teachers at school and parents at home significantly contribute to improving the social-emotional abilities of 4–5-year-old children